Conviviality and its impact on business relationships: insights into an entrepreneurial textile-clothing community. Issue 3 (3rd July 2017) - Guercini, Simone; Becagli, Claudio; Ranfagni, Silvia
Abstract: Entrepreneurial communities are social units that share values, experiences, rituals and traditions. In these communities, conviviality represents a socialization tool, which can foster a sense of belonging through the development of social relations among its members. Since conviviality has a social impact, it can be related to the phenomenon of "embeddedness" whenever the social relations that it produces incorporate business relations. Drawing on an appropriate literature review and on the case analysis of a community of young entrepreneurs operating in the textile district of Prato (Italy), we propose to investigate how conviviality affects social relations making them interactive contexts to animate business relations.